Drimanes and other terpenoids from the fern Thelypteris hispidula (Decne) REED - Socolsky, Cecilia (2005)
The drimane‐type sesquiterpenoids (−)‐polygodial (1), (−)‐isopolygodial (4), drimenin (5), and isodrimenin (6) were isolated from a pungent Argentine collection of the fern Thelypteris hispidula, along with other terpenoids. As the mentioned drimanes have been previously found in liverworts, the present results strongly support the theory that Pteridophytes and Bryophytes share the same line of evolution. Our present investigations indicate that two chemotypes of T. hispidula are widespread in the northwest of Argentina. Plants belonging to the pungent chemotype contain drimanes, while nonpungent plants lack drimanes